Perlindungan Data Pribadi dalam Era Internet of Things: Studi Kasus Kebocoran Data Lion Air - Josephine Yenni Sijabat (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The rapid development of the Internet of Things (IoT) in Indonesia brings new challenges in personal data protection. This study aims to analyze the suitability of the legal framework in Indonesia in protecting personal data collected by IoT devices. This study identifies data collection and use practices, as well as uncovers existing legal loopholes. This study intends to conduct an in-depth analysis of the level of compliance with personal data protection laws in the context of IoT solutions. The normative legal research method with the library search technique is to search for journal or article materials related to the title and theme that the author is studying. Therefore, this study has a strategic goal to investigate the extent to which applicable regulations can be effectively implemented in the IoT ecosystem, with a special focus on security and privacy aspects that are the main pillars of personal data protection regulations. Based on these findings, this study provides policy recommendations to improve personal data protection in the IoT era, such as the need for a revision of the ITE Law, strengthening supervision by related institutions, or increasing public awareness.